1994
DOI: 10.1161/01.atv.14.7.1040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of notoginsenoside R1 on the synthesis of tissue-type plasminogen activator and plasminogen activator inhibitor-1 in cultured human umbilical vein endothelial cells.

Abstract: Among other Chinese herb drugs, Panax notoginseng is used to treat cardiovascular diseases. To elucidate any possible effects of this drug on the hemostatic system in vitro, we analyzed the influence of one of its major active constituents on fibrinolytic parameters of cultured human umbilical vein endothelial cells (HUVECs). When confluent cultures of HUVECs (passages 2 to 3) were conditioned with purified notoginsenoside Rl (NR1), a dose-(0.01 to 100 fig NRl/mL) and time-dependent increase in tissue-type pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…In this regard, it is interesting that P. notoginseng which we found to inhibit the secretion of TNF-a has been used to treat various vascular diseases and cardiac pain. Zhang et al reported that notoginsenoside R1 from P. notoginseng has a fibrinolytic activity by increasing tissue-type plasminogen activator and decreasing plasminogen activator inhibitor-1 [24]. More recently, the decrease of total cholesterol, tri-glycerides and fibrinogen in blood by the treatment of P. notoginseng pulverized root has been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is interesting that P. notoginseng which we found to inhibit the secretion of TNF-a has been used to treat various vascular diseases and cardiac pain. Zhang et al reported that notoginsenoside R1 from P. notoginseng has a fibrinolytic activity by increasing tissue-type plasminogen activator and decreasing plasminogen activator inhibitor-1 [24]. More recently, the decrease of total cholesterol, tri-glycerides and fibrinogen in blood by the treatment of P. notoginseng pulverized root has been reported [25].…”
Section: Discussionmentioning
confidence: 99%
“…1). It has exhibited various health promotion activities, including being neuroprotective (Gu et al, 2009), hepatic protective (Chen et al, 2008), cardiovascular protective (Zhang et al, 1994), and exhibiting immune stimulation effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is also contained in several famous Chinese traditional formula, such as "Yunnan Baiyao" which is used for treatment of injury induced trauma and bleeding, and "Pian Zi Huang" used to treat hepatitis. Current pharmacological studies revealed that P. notoginseng and its saponins possess anticarcinogenic [4,5] and hepatoprotective [6] properties, as well as protective effects on cardiovascular and cerebrovascular diseases [7][8][9].…”
Section: Introductionmentioning
confidence: 99%